Whole blood samples for faster real-time PCR analysis of thrombophilic mutations in SARS-CoV-2 virus positive patients - Beránek, M; Koblížek, V; Dulíček, P; Hegerová, J; Palička, V (Physiological research, 2022)
High incidence of thrombosis and venous thromboembolism was reported in patients with COVID-19. In this study, we focused on analysis of thrombophilic mutations performed without a standard DNA extraction step. In one hundred of COVID-19 positive outpatients, real-time PCR for Leiden mutation in the FV gene and G20210A mutation in the FII gene was carried out from DNA extracts and modified whole blood samples, and their cycle threshold (Ct) values were evaluated. In the extracts, healthy homozygotes (wt/wt), heterozygotes (M/wt), and homozygous carriers of Leiden mutation (M/M) provided median Ct values of 18.5, 19.4/22.0, and 20.9. In the whole blood, Ct values were 25.3 (wt/wt), 24.8/27.2 (M/wt), and 26.9 (M/M). Median Ct values for G20210A in the extracts were 19.6 for homozygotes (wt/wt), and 19.7/20.4 for heterozygous carriers. The whole blood samples provided Ct values of 23.9 in healthy homozygotes and 26.3/27.2 in heterozygotes for G20210A mutation. No homozygous subjects for G20210A and no double heterozygotes (for Leiden and G20210A mutations) were found. Despite significant differences in the Ct values, genotyping showed complete result concordance of the DNA extracts and the whole blood samples. The integrity and amplificability of DNA molecules in the whole blood samples during 28 days of deep freezing, interrupted by four cycles of thawing, did not significantly change. In conclusion, we demonstrated a new protocol for the detection of the thrombophilic mutations via real time PCR on the modified whole blood of COVID-19 positive patients. The blood modification was reliable, easy, cheap, and saving costs and turnaround time of the whole laboratory process.
Keywords: mutace; kvantitativní polymerázová řetězová reakce; Risk Factors; faktor V; Factor V; Real-Time Polymerase Chain Reaction; Thrombophilia; SARS-CoV-2; protrombin; lidé; Humans; trombofilie; rizikové faktory; DNA; Prothrombin; Mutation; testování na COVID-19; COVID-19 Testing; COVID-19